Application of modified socket-shield technique in immediate implant placement in the esthetic zone of anterior teeth - WU Haoying; WANG Fang (Kouqiang hemian waike zazhi)
[Objective:] To evaluate the clinical effect of the modified socket-shield technique (MSST) in the immediate implant placement of single teeth in the anterior esthetic zone, and to discuss the related technical points. [Methods:] Five cases of immediate implant placement using MSST in the anterior esthetic zone from December 2022 to December 2023 were reviewed. The alveolar bone remodeling around implants was evaluated by imaging analysis. The esthetic effect of peri-implant soft tissue was evaluated by pink esthetic score (PES). The visual analogue scale (VAS) was used to assess the patients' subjective evaluation of the postoperative reaction (pain, swelling, etc.), the final repair effect and the whole treatment process. [Results:] Radiographic analysis showed that all implant sites achieved good osseointegration. The average vertical change of the labial alveolar bone of the implant at 6 months postoperatively was (0.18±0.15) mm. The average horizontal changes of labial alveolar bone at 2, 4, and 6 mm apical to the implant shoulder were (0.39±0.17), (0.18±0.23), (0.22±0.18) mm, respectively. The average change of alveolar bone width at implant shoulder level was (0.10±0.10) mm. The average PES score was (12.40±1.34) points, and satisfactory esthetic results were obtained in all implant sites. The VAS score showed that the subjective satisfaction of patients was high. [Conclusion:] The application of MSST in immediate implant placement in the anterior aesthetic area can effectively maintain the bone volume and soft tissue contour around the implant, and is a feasible technical solution for aesthetic area implant restoration.